Anticoccidial potential of Ageratum conyzoides and its effect on Blood parameters of experimentally infected Broiler Chickens - HUSSAIN, K; ABBAS, RZ; ABBAS, A; SAMIULLAH, K; AHMED, T; SIDDIQUE, F; MOHSIN, M; REHMAN, A; RAHMAN, A.UL; WAQAS, MU (Journal of the Hellenic Veterinary Medical Society, 2021)
Coccidiosis is an infectious parasitic disease of poultry which causes heavy economic losses to commercial poultry industry. Coccidiosis has been generally controlled by using different synthetic anticoccidial drugs but, due to development of resistance to these drugs this method is losing its effectiveness. Exploration of novel and alternative compounds against avian coccidiosis is need of time now a days. In this regard, medicinal plants can serve as substitute to these synthetic anticoccidials. Thus, to find out alternative novel agents, current research was designed to evaluate the anticoccidial potential of Ageratum conyzoides extract (ACE). For in vivo experiment, 105 broiler chicks were purchased and further divided into 7 sub-groups (15 birds in each group). At 7th day of experiment, Groups A, B and C were fed with plant extract at 100, 200 and 300 mg/kg respectively. Group D was supplemented with Vitamin-E while, Group E and F remained as infected medicated and infected un-medicated control groups and served with standard medicine (Baycox®) and Phosphate Buffer Saline (PBS) respectively. Moreover, Group G served as normal control group. At day 14th of experiment, all groups except rom Group G were orally infected with 60,000 sporulated oocysts of mixed Eimeria species. Anticoccidial potential of ACE was evaluated on the basis of lesion scores, fecal scores, oocyst scores and feed conversion ratio. Furthermore, the effect of ACE on the serum chemistry was also evaluated to check toxicity of plant extract if any. The results were compared with standard medicine (Baycox®). On the basis of results, ACE showed anticoccidial activity by reducing fecal, lesion and oocyst scores in infected chicks (P<0.05). ACE also improved FCR of infected chicks. Moreover, ACE exhibited positive effects on serum chemistry of broiler chickens (P<0.05).